The Urgency of Nonformal Islamic Education in Improving the Quality of Madrasah Aliyah in Sungguminasa, Gowa Regency - Mukhtar Mas’ud (Program Pascasarjana UIN Sumatera Utara, 2023)
This study aims to analyze the urgency of nonformal education in improving the educational quality of Madrasah Aliyah students in Sungguminasa, Gowa Regency. The study is grounded in the reality of limited instructional time allocation in madrasahs, particularly in foreign language mastery and life skills development, which therefore requires reinforcement through nonformal education pathways. This research employs a descriptive qualitative approach with a multidisciplinary perspective encompassing normative theology, pedagogy, psychology, and sociology. The research was conducted in Sungguminasa, Gowa Regency, South Sulawesi. Primary data sources consisted of students, teachers, managers of nonformal education institutions, officials from the Ministry of Religious Affairs and the Department of Education, as well as members of the community. Secondary data were obtained from literature reviews and policy documents. Data were collected through participatory observation, in-depth interviews, documentation studies, and triangulation. The data were analyzed using the Miles and Huberman model. The findings reveal that: (1) the profile of nonformal education in Sungguminasa is supported by strong theological, normative, and juridical foundations, although it continues to face paradigmatic and structural constraints; (2) the quality of nonformal education is pursued through the implementation of national standards in terms of input, process, output, and outcome; and (3) nonformal education plays a highly significant role in developing learning strategies, academic competence, cognitive-affective-psychomotor domains, character, and students’ personalities. The study concludes that nonformal education is an essential necessity that must be synergistically integrated with formal and informal education to achieve holistic and sustainable educational quality among Madrasah Aliyah students.